Improving Mitra Bakti Husada Vocational School's Learning Quality Through School-Based Management - Dewi Gunherani (Universitas Pendidikan Ganesha, 2023)
The School-Based Management (SBM)-based Education Quality Improvement Program must be carried out continuously to maintain public trust so that the quality of education will produce professionals who can fill jobs according to their profession in the community. This study aims to analyze the quality of learning at SMK based on school-based management. This type of research is qualitative. The research approach used in this research is qualitative research. Research instruments were used as interview guidelines (questionnaires), observation guidelines, and documentation to obtain research data. The sample data are school residents: the principal, teachers, education staff, and the school committee. The data analysis technique uses descriptive qualitative analysis. The result of the research is that government policies have improved educational outcomes through 4 stages of design, namely evaluation of educational achievements, planning of educational evaluation, improving the quality of education, and monitoring the quality of education. SMK has implemented 4 main principles of School-Based Management/SBM: the Principle of Autonomy, the Principle of Flexibility, the Principle of Participation, and the Principle of Initiative.